Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT) and Alberta Infant Motor Scale (AIMS): Validity and Responsiveness. Issue 11 (1st November 2015) - Dumas, Helene M.; Fragala-Pinkham, Maria A.; Rosen, Elaine L.; Lombard, Kelly A.; Farrell, Colleen
Abstract : Background: Although preliminary studies have established a good psychometric foundation for the Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT) for a broad population of youth with disabilities, additional validation is warranted for young children. Objective: The study objective was to (1) examine concurrent validity, (2) evaluate the ability to identify motor delay, and (3) assess responsiveness of the PEDI-CAT Mobility domain and the Alberta Infant Motor Scale (AIMS). Methods: Fifty-three infants and young children (<18 months of age) admitted to a pediatric postacute care hospital and referred for a physical therapist examination were included. The PEDI-CAT Mobility domain and the AIMS were completed during the initial physical therapist examination, at 3-month intervals, and at discharge. A Spearman rank correlation coefficient was used to examine concurrent validity. A chi-square analysis of age percentile scores was used to examine the identification of motor delay. Mean score differences from initial assessment to final assessment were analyzed to evaluate responsiveness. Results: A statistically significant, fair association ( r s =.313) was found for the 2 assessments. There was no significant difference in motor delay identification between tests; however, the AIMS had a higher percentage of infants with scores at or below the fifth percentile. Participants showed significant changes from initial testing to final testing on the PEDI-CAT Mobility domain and the AIMS. Limitations: This study included only young patients (<18 months of age) in a pediatric postacute hospital; therefore, the generalizability is limited to this population. Conclusions: The PEDI-CAT Mobility domain is a valid measure for young children admitted to postacute care and is responsive to changes in motor skills. However, further item and standardization development is needed before the PEDI-CAT is used confidently to identify motor delay in children <18 months of age.